Legisla????o e educa????o profissional: um estudo sobre documentos de orienta????o curricular no Instituto Federal de Educa????o, Ci??ncia e Tecnologia de S??o Paulo - Pereira Junior, Ademar Bernardes (2018)
The object of this research articles around professional education, curricular orientation documents, pedagogy of skills and work as an educational principle. The bibliographical and documentary research had as main objective to understand how the Instituto Federal de Educa????o, Ci??ncia e Tecnologia de S??o Paulo, during the period 1998-2014, incorporated, in its curricular orientation documents, the collision between different conceptions of formation, expressed in the pedagogy of skills and work as an educational principle. The research was oriented in the perspective that the school institutions do not incorporate in a simple and direct way the principles and orientations defined by the national curricular documents, but that, throughout this process, changes and reformulations occur that appear as expression of culture and form specific, and which need to consider in the investigative processes. Culture and school form that produce over time, through processes of incorporation, appropriation and denial, and that take shape in everyday school practices. In this sense, the understanding of the process of elaboration of the curricular documents implied: in the analysis of the legal framework that has been constituted the professional education in Brazil since the Federal Constitution of 1998, especially reports, normative instructions and resolutions; in analyzing the polysemy that characterizes the concept of competence and the way it is incorporated into the educational debate; to show which assumptions are guiding the thesis of work as an educational principle and in what form it gains density in the educational debate. Finally, in the description and analysis of documents elaborated between 1998 and 2013, which defined in the broad and internal context, the politics of curricular organization. In this context of the research we are faced with the way in which the so-called pedagogy of competences and the thesis of work as an educational principle have gained historical density as the guiding principle of the curricular policy of the former CEFET, the current IFSP.